2017
DOI: 10.1016/j.omtn.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Fine and Predictable Tuning of TALEN Gene Editing Targeting for Improved T Cell Adoptive Immunotherapy

Abstract: Using a TALEN-mediated gene-editing approach, we have previously described a process for the large-scale manufacturing of “off-the-shelf” CAR T cells from third-party donor T cells by disrupting the gene encoding TCRα constant chain (TRAC). Taking advantage of a previously described strategy to control TALEN targeting based on the exclusion capacities of non-conventional RVDs, we have developed highly efficient and specific nucleases targeting a key T cell immune checkpoint, PD-1, to improve engineered CAR T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…However, these therapies face multiple challenges, including tumor accessibility, tumor-dependent inhibitory signals, and a microenvironment that is hostile to T cells. To overcome these obstacles, CAR T cells have been engineered to remove inhibitory receptors [1][2][3] , to express costimulatory molecules 3 and chemokine receptors 4,5 , or to secrete immunostimulatory factors such as checkpoint inhibitors 6 or cytokines 7 . In particular, cytokine secretion by so called Armored or Truck CAR T cells 7,8 is a highly promising strategy for improving CAR T cell function.…”
mentioning
confidence: 99%
“…However, these therapies face multiple challenges, including tumor accessibility, tumor-dependent inhibitory signals, and a microenvironment that is hostile to T cells. To overcome these obstacles, CAR T cells have been engineered to remove inhibitory receptors [1][2][3] , to express costimulatory molecules 3 and chemokine receptors 4,5 , or to secrete immunostimulatory factors such as checkpoint inhibitors 6 or cytokines 7 . In particular, cytokine secretion by so called Armored or Truck CAR T cells 7,8 is a highly promising strategy for improving CAR T cell function.…”
mentioning
confidence: 99%
“…For ZFNs this has included improving cleavage activity by reducing undesired homodimerization of the ZFN pairs through modification of FokI domains [128]. TALEN technologies have focused on virtually eliminating low frequency off‐site effects by replacing naturally occurring repeat‐variable di‐residues (RVDs) within modular TALE arrays (which are responsible for specifying the target nucleotide for binding), using unconventional TALEs not present within the natural TALE repertoire [129–131]. These have significantly improved targeting specificity and offer a more simplified means to facilitate multiplex editing strategies for therapeutic use.…”
Section: Off‐target Effects and Preclinical Developments In Gene Editmentioning
confidence: 99%
“…Immune checkpoint receptor PD-1 can also be upregulated in activated CAR-T cells, and, recently, various studies have reported that suppression of PD-1 in parallel to CAR-T therapy could be beneficial. Further, genome engineering techniques such as CRISPR/Cas9 [48] and TALEN [49] were used to generate PD-1-deficient CAR-T cells. CAR-T cells were also modified to secrete PD-1-blocking scFv, which improved the antitumor response.…”
Section: Chimeric Antigen Receptor (Car)-t Car-nk Cellsmentioning
confidence: 99%